Complexity of immunobiology of tumor necrosis factor and novel anti-TNF therapy - S. А. Nedospasov (Медицинская иммунология, 2023)
Tumor Necrosis Factor (TNF) was discovered almost 50 years ago as “serum factor” detected in mice following infections or administration of bacterial lipopolysaccharide (LPS), with a remarkable anti-tumor effect. Molecular cloning showed that this activity is mediated by a small protein (17 kDa), which belongs to a wide plethora of cytokines. Due to the particular organization of the TNF gene coding sequence, all cells producing soluble TNF also carry a membrane-bound cytokine on their surface. The physiological effects of TNF are mediated by signaling through two types of highly specific receptors. Despite established protective and homeostatic functions of TNF, when overproduced systemically or locally, it can trigger pathologies ranging from septic shock to autoimmune diseases. Therefore, in clinical immunotherapy there were not the TNF agonists, which were expected to induce anti-tumor effects, but rather the antagonistic blockers, that proved effective in a wide range of autoimmune diseases with an inflammatory component. Our studies in mice based on the technologies of reverse genetics and experimental disease models, revealed a paradoxical feature of TNF: some cellular sources of this cytokine (such as myeloid cells) promoted diseases, while other cell types (such as T lymphocytes) produced a protective form of the same cytokine. There are several possible mechanistic explanations for this phenomenon. On the one hand, the "pathogenic" cytokine is produced in a soluble form and can exert systemic effects via broadly expressed TNFR1. On the other hand, protective functions are mediated by the membrane-bound TNF via TNFR2. Systemic anti-cytokine therapy is known to be accompanied by undesirable side effects, which can hypothetically be explained by the neutralization of these protective functions. Thus, we developed prototypes of TNF blockers which limit the bioavailability of this cytokine only from its main “pathogenic” source – myeloid cells. This type of inhibitors, called MYSTI, represent bispecific mini-antibodies binding both TNF and a surface marker on myeloid cells and lacking the Fc domain. MYSTI retain newly synthesized TNF on the surface of the producing cell and then internalize it. This novel type of immunotherapy drug has already shown efficacy in a number of experimental disease models.